Answer:
ez, answer choice number 4
Step-by-step explanation:
y=-1/8x(this is the slope) -4(this is the y intercept
Answer:
y = 4/3x - 4
Step-by-step explanation:
to find the equation of a line with 2 points, we use the slope formula which is:
![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
we will use (6,4) as
and we will use (-3,-8) as
. we plug this into the slope formula:
![\frac{-8-4}{-3-6}](https://tex.z-dn.net/?f=%5Cfrac%7B-8-4%7D%7B-3-6%7D)
-8 - 4 = -12
-3 - 6 = -9
the slope is ![\frac{-12}{-9}](https://tex.z-dn.net/?f=%5Cfrac%7B-12%7D%7B-9%7D)
but we can simplify this further by dividing the fraction by -3
-12 / -3 = 4
-9 / -3 = 3
the simplified version of the slope is ![\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
we can write this in slope-intercept form which is y =mx + b, with b being the y intercept and m being the slope
y = 4/3x + b <--- we need to solve for <em>b</em> in order to find the y intercept, so substitute x & y for a point on the line, we can use any point we are given, but for this example i will use (6,4)
4 = 4/3(6) + b < multiply 4/3 x 6
4 = 8 + b < subtract 8 from both sides
-4 = b
our y intercept would be (0,-4)
the equation looks like the following:
y = 4/3x - 4, which is our answer
<h2>SOLVING</h2>
![\Large\maltese\underline{\textsf{A. What is Asked}}](https://tex.z-dn.net/?f=%5CLarge%5Cmaltese%5Cunderline%7B%5Ctextsf%7BA.%20What%20is%20Asked%7D%7D)
Find the point-slope equation of the line, with the info given
![\Large\maltese\underline{\textsf{This problem has been solved}}](https://tex.z-dn.net/?f=%5CLarge%5Cmaltese%5Cunderline%7B%5Ctextsf%7BThis%20problem%20has%20been%20solved%7D%7D)
Formula used, ![\bf y-y1=m(x-x1)](https://tex.z-dn.net/?f=%5Cbf%20y-y1%3Dm%28x-x1%29)
| result
![\rule{300}{1.7}](https://tex.z-dn.net/?f=%5Crule%7B300%7D%7B1.7%7D)
![\boxed{\bf aesthetic\not101}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbf%20aesthetic%5Cnot101%7D%7D)
Ooh, fun
geometric sequences can be represented as
![a_n=a(r)^{n-1}](https://tex.z-dn.net/?f=a_n%3Da%28r%29%5E%7Bn-1%7D)
so the first 3 terms are
![a_1=a](https://tex.z-dn.net/?f=a_1%3Da)
![a_2=a(r)](https://tex.z-dn.net/?f=a_2%3Da%28r%29)
![a_2=a(r)^2](https://tex.z-dn.net/?f=a_2%3Da%28r%29%5E2)
the sum is -7/10
![\frac{-7}{10}=a+ar+ar^2](https://tex.z-dn.net/?f=%5Cfrac%7B-7%7D%7B10%7D%3Da%2Bar%2Bar%5E2)
and their product is -1/125
![\frac{-1}{125}=(a)(ar)(ar^2)=a^3r^3=(ar)^3](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B125%7D%3D%28a%29%28ar%29%28ar%5E2%29%3Da%5E3r%5E3%3D%28ar%29%5E3)
from the 2nd equation we can take the cube root of both sides to get
![\frac{-1}{5}=ar](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B5%7D%3Dar)
note that a=ar/r and ar²=(ar)r
so now rewrite 1st equation as
![\frac{-7}{10}=\frac{ar}{r}+ar+(ar)r](https://tex.z-dn.net/?f=%5Cfrac%7B-7%7D%7B10%7D%3D%5Cfrac%7Bar%7D%7Br%7D%2Bar%2B%28ar%29r)
subsituting -1/5 for ar
![\frac{-7}{10}=\frac{\frac{-1}{5}}{r}+\frac{-1}{5}+(\frac{-1}{5})r](https://tex.z-dn.net/?f=%5Cfrac%7B-7%7D%7B10%7D%3D%5Cfrac%7B%5Cfrac%7B-1%7D%7B5%7D%7D%7Br%7D%2B%5Cfrac%7B-1%7D%7B5%7D%2B%28%5Cfrac%7B-1%7D%7B5%7D%29r)
which simplifies to
![\frac{-7}{10}=\frac{-1}{5r}+\frac{-1}{5}+\frac{-r}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B-7%7D%7B10%7D%3D%5Cfrac%7B-1%7D%7B5r%7D%2B%5Cfrac%7B-1%7D%7B5%7D%2B%5Cfrac%7B-r%7D%7B5%7D)
multiply both sides by 10r
-7r=-2-2r-2r²
add (2r²+2r+2) to both sides
2r²-5r+2=0
solve using quadratic formula
for
![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
![x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
so
for 2r²-5r+2=0
a=2
b=-5
c=2
![r=\frac{-(-5) \pm \sqrt{(-5)^2-4(2)(2)}}{2(2)}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B-%28-5%29%20%5Cpm%20%5Csqrt%7B%28-5%29%5E2-4%282%29%282%29%7D%7D%7B2%282%29%7D)
![r=\frac{5 \pm \sqrt{25-16}}{4}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B5%20%5Cpm%20%5Csqrt%7B25-16%7D%7D%7B4%7D)
![r=\frac{5 \pm \sqrt{9}}{4}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B5%20%5Cpm%20%5Csqrt%7B9%7D%7D%7B4%7D)
![r=\frac{5 \pm 3}{4}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B5%20%5Cpm%203%7D%7B4%7D)
so
![r=\frac{5+3}{4}=\frac{8}{4}=2](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B5%2B3%7D%7B4%7D%3D%5Cfrac%7B8%7D%7B4%7D%3D2)
or
![r=\frac{5-3}{4}=\frac{2}{4}=\frac{1}{2}](https://tex.z-dn.net/?f=r%3D%5Cfrac%7B5-3%7D%7B4%7D%3D%5Cfrac%7B2%7D%7B4%7D%3D%5Cfrac%7B1%7D%7B2%7D)
use them to solve for the value of a
![\frac{-1}{5}=ar](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B5%7D%3Dar)
![\frac{-1}{5r}=a](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B5r%7D%3Da)
try for r=2 and 1/2
![a=\frac{-1}{10}](https://tex.z-dn.net/?f=%20a%3D%5Cfrac%7B-1%7D%7B10%7D)
or
![a=\frac{-2}{5}](https://tex.z-dn.net/?f=a%3D%5Cfrac%7B-2%7D%7B5%7D)
test each
for a=-1/10 and r=2
a+ar+ar²=
![\frac{-1}{10}+\frac{-2}{10}+\frac{-4}{10}=\frac{-7}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B10%7D%2B%5Cfrac%7B-2%7D%7B10%7D%2B%5Cfrac%7B-4%7D%7B10%7D%3D%5Cfrac%7B-7%7D%7B10%7D)
it works
for a=-2/5 and r=1/2
a+ar+ar²=
![\frac{-2}{5}+\frac{-1}{5}+\frac{-1}{10}=\frac{-7}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B-2%7D%7B5%7D%2B%5Cfrac%7B-1%7D%7B5%7D%2B%5Cfrac%7B-1%7D%7B10%7D%3D%5Cfrac%7B-7%7D%7B10%7D)
it works
both have the same terms but one is simplified
the 3 numbers are
![\frac{-2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B-2%7D%7B5%7D)
,
![\frac{-1}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B5%7D)
, and
Answer:
f(-2) = 3
Step-by-step explanation:
Look at the graph when x = -2, f(-2) = 3